The contribution of aestivating mosquitoes to the persistence of Anopheles gambiae in the Sahel - Traoré Sékou F; Diallo Moussa; Yaro Alpha; Kassogué Yaya; Timbine Seydou; Dao Adama; Adamou Abdoulaye; Huestis Diana L; Lehmann Tovi (Malaria Journal, 2011)
Abstract Background Persistence of African anophelines throughout the long dry season (4-8 months) when no surface waters are available remains one of the enduring mysteries of medical entomology. Recent studies demonstrated that aestivation (summer diapause) is one mechanism that allows the African malaria mosquito, Anopheles gambiae, to persist in the Sahel. However, migration from distant localities - where reproduction continues year-round - might also be involved. Methods To assess the contribution of aestivating adults to the buildup of populations in the subsequent wet season, two villages subjected to weekly pyrethrum sprays throughout the dry season were compared with two nearby villages, which were only monitored. If aestivating adults are the main source of the subsequent wet-season population, then the subsequent wet-season density in the treated villages will be lower than in the control villages. Moreover, since virtually only M-form An. gambiae are found during the dry season, the reduction should be specific to the M form, whereas no such difference is predicted for S-form An. gambiae or Anopheles arabiensis. On the other hand, if migrants arriving with the first rain are the main source, no differences between treated and control villages are expected across all members of the An. gambiae complex. Results The wet-season density of the M form in treated villages was 30% lower than that in the control (P < 10-4, permutation test), whereas no significant differences were detected in the S form or An. arabiensis. Conclusions These results support the hypothesis that the M form persist in the arid Sahel primarily by aestivation, whereas the S form and An. arabiensis rely on migration from distant locations. Implications for malaria control are discussed.